Mapping the School Environment: Exploring Key Elements through Students' and Teachers' Perspectives - Tamang, Tshering Om; Seday, Kinley; Gayphel, Karma (Journal of Educational Management Research, 2025)
This study investigated the elements within educational environments that students and teachers perceive as critical for advancing gender equality and social inclusion. Using a Participatory Action Research (PAR) methodology, focus group interviews were conducted with students (boys and girls) and teachers across five schools in Samtse Dzongkhag. Participants were asked to identify and reflect on the key aspects they consider important for promoting inclusion and gender equality within their school environments. The findings revealed distinct priorities between the groups. Boys and teachers primarily emphasized the importance of physical infrastructure, such as school buildings, playgrounds, and gender-sensitive facilities, viewing these as essential to fostering gender equality. In contrast, girls highlighted social and emotional aspects, including equal treatment, access to resources, and the need for a supportive school culture. The study underscored the importance of integrating both physical and non-physical elements to create inclusive and equitable educational spaces. These insights provide valuable evidence to inform practices and policies that promote gender equality and social inclusion in schools.